2007
DOI: 10.1021/ol070092y
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Efficient Heterogeneous Copper Catalysts for Enantioselective C−H Carbene Insertion

Abstract: Immobilized box-Cu complexes are able to efficiently catalyze the insertion of a carbene, from methyl phenyldiazoacetate, into C-H bonds of THF, with high enantioselectivity (up to 88% ee). The immobilization not only allows recovery and reuse of the enantioselective catalyst but also provides an improvement in the selectivities from the values obtained in solution, probably due to a confinement effect of the bidimensional support. [reaction: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 22 publications
0
62
0
Order By: Relevance
“…While copper catalysts have previously been employed in C-H insertion processes, 31,114 enantioselectivities achieved have been, in general, moderate, with the highest asymmetric induction being noted for intermolecular C-H insertion in the presence of an immobilised Cu(I) bis-oxazoline ligand (88% ee). 30 Thus, this publication represents the highest level of enantiocontrol achieved to date in a copper-mediated C-H insertion reaction. As seen in Table 26 (entries a-e), enantioselectivities of up to 98% ee were realised for the decomposition of various substituted α-diazosulfones.…”
Section: Sulfur-containing Heterocycle Synthesismentioning
confidence: 95%
See 1 more Smart Citation
“…While copper catalysts have previously been employed in C-H insertion processes, 31,114 enantioselectivities achieved have been, in general, moderate, with the highest asymmetric induction being noted for intermolecular C-H insertion in the presence of an immobilised Cu(I) bis-oxazoline ligand (88% ee). 30 Thus, this publication represents the highest level of enantiocontrol achieved to date in a copper-mediated C-H insertion reaction. As seen in Table 26 (entries a-e), enantioselectivities of up to 98% ee were realised for the decomposition of various substituted α-diazosulfones.…”
Section: Sulfur-containing Heterocycle Synthesismentioning
confidence: 95%
“…A range of additional chiral complexes have been shown to be efficient catalytic systems for intermolecular C-H insertion processes including a recyclable fluorous chiral rhodium(II) complex, 66 and bis(oxazoline)-copper complexes. 30 More recently, the adamantylglycinederived chiral tetracarboxylate complex Rh 2 (S-PTAD) 4 has been introduced as an additional catalytic choice for such transformations. 67 While Rh 2 (S-DOSP) 4 has shown exceptional results for the majority of reactions of donor/acceptor carbenoids discussed above, it is not an effective catalytic option when the diazo acceptor group is changed from a methyl ester to another acceptor group.…”
Section: Figure 20mentioning
confidence: 99%
“…The copper content was only slightly lower than that of the fresh catalyst (0.19 vs 0.21 mmol/g), with similar N/Cu ratio (2.1 vs 2.3) and a significant increase in the carbon content (C/N ratio 17.6 instead of the starting 7.7), pointing again to the poisoning with byproducts. 23 These poor stereoselectivity results, mainly in comparison with the higher enantioselectivity obtained with cyclic ethers, 13,14 are probably due to the lack of bulky groups in both reactants and to the conformational freedom of the open chain ether. To the best of our knowledge this reaction had not been described in the literature.…”
Section: Reaction Of Methyl P-bromophenyldiazoacetate With Benzyl Metmentioning
confidence: 99%
“…8,9 Regarding copper catalyzed enantioselective intermolecular reactions, carbene insertions into O-H bonds were firstly described, 10 whereas results were improved and extended to other X-H bonds by using spiro-bis(oxazoline) ligands. 11 After an early attempt of enantioselective intermolecular insertion into C-H bonds, with poor results, 12 our group described for the first time a successful intermolecular insertion into THF, 13 extended to other cyclic ethers with enantioselectivities from low to moderate depending on the structure of the substrate. 14 In fact a good part of this moderate success is due to the use of complexes immobilized by electrostatic interactions 15 on a synthetic clay (laponite) able to modulate not only the catalytic activity but also the stereochemical course of the catalyzed reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that immobilized catalysts can afford additional advantages related to site-isolation or to the possibility of using them as true multitask catalysts. 9 More recently, it has been shown that the support can be used as an active part of the enantioselection process, 10 leading to 55 catalytic reactions with improved stereoselectivity 11 or even with a reversal in the stereochemical result in comparison with the behavior of the same catalysts in solution. 12 The easy separation and purification of the catalyst, as well as the improved activity and selectivity are clearly desirable 60 objectives of Green Chemistry.…”
Section: Introductionmentioning
confidence: 99%